The reasons of Central Asian youth involvement in terrorist and extremist organizations (International relations and international law Journal, 2018)
Terrorism has become one of the factors of socio-political life, it has become one of the main threats to security in the world. Never before have terrorist attacks brought so many victims and devastations of a huge scale at one time, were not so professionally prepared and coordinated, did not attract such heavy moral, material, financial, political and environmental consequences. However, the problem of terrorism and extremism in modern society is worsened by the fact that more and more terrorist organizations involve young people in their activities. Through the influence of various factors, such as: social, political, economic, the most vulnerable to the ideological influence of young people, replenishes the ranks of extremist and terrorist groups, whose leaders use and manipulate them for their own purposes. Young people become a focal group for terrorists, as the impact on the immature psyche requires less work and gives more success. As a result, they simply become victims, in view of their insolvency and social, material insecurity. The young generation, by its very nature, age and position in society, has those features and features of thinking and behavior that, in certain socio-psychological conditions and purposeful influences, shape extremist personalities. Today there are about 500 illegal terrorist organizations in the world and the activities of extremist individuals, groups and organizations are increasing every day. A distinctive feature of modern international terrorism is globalization, which is based on extremist ideology. The world community is concerned about the growth of terrorist activity which is caused by numerous victims and huge material damage. The conducted research allows to consider the main reasons for participation of young people living in the countries of Central Asia in the activities of terrorist and extremist organizations. The materials of the article can be useful in a comprehensive study of the problem of terrorism and extremism in the territory of the Central Asian region.Key words: terrorism, extremism, youth, Central Asia, antiterrorist activity, recruitment, reasons for involvement.